Politeness and Impoliteness in Online Comments by Newspaper Readers - Oloyede, I. Bayo (Legattext Publishing Company Limited, 2011)
Internet freedom, which essentially is the freedom to connect, has been linked with the fundamental human rights framework because the internet is a virtual platform for the exhibition of freedoms of assembly, expression and association, given that these rights are expressible as well in cyberspace just as they are in real space. Arguably, ensuring that these rights extend to the cyberspace could preserve the promises the internet holds as a platform for development in terms of ideas generation, innovation, networking and connections and economic growth. While this right is being enjoyed by some, a number of trends are beginning to emerge. This includes acts of impoliteness in the addresses of people who post comments online after reading a story or other publications. It becomes therefore necessary to establish the presence of such acts, regarded as face threatening acts in politeness research, in online comments of readers of online Nigerian newspapers. This is what this paper has attempted to do.